(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To report radiological outcomes of short segment posterior fixation with screws in intermediate vertebra. Methods: This descriptive retrospective study was conducted in Nishtar Hospital Multan from January 2020 to July 2021. Patients with thoraco-lumbar spine (T10-L2 vertebra) burst fractures who underwent short segment posterior fixation with screws in fractured vertebra were included. Radiological outcomes in terms of Cobb angle and anterior vertebral height on pre-operative, immediate post-operative and 1-year follow-up x-rays were calculated and compared using paired sample t-test. Results: This study included 40 patients (32 males and 8 females) with a mean age of 33.47±13.33 years. Majority of cases involved fracture of D12 vertebra (45%). The mean preoperative kyphotic angle according to Cobb’s method was 24.58° ± 3.4° which showed significant improvement to 6.6° ± 1.33° following instrumentation (p<0.0001). The average preoperative vertebral height was 59.48% which improved significantly to 88.7% (p<0.0001). However, at final follow-up, there was loss of correction which was evident in terms of increased Cobb angle to 9.7° and loss of anterior vertebral height to 79%. The difference between pre-operative and follow-up measurements for both Cobb angle and anterior vertebral height was significant (p<0.0001). There were no incidence of implant failure or screw pull-out. Conclusion: The results of this study demonstrate short segment posterior spinal instrumentation with screws in fractured vertebra provide excellent correction of kyphotic deformity.